Evidence of subduction-related thermal and compositional heterogeneity below the United States from transition zone receiver functions - Maguire,R; Ritsema,J; Goes,S (Geophysical Research Letters, 2018)
The subduction of the Farallon Plate has altered the temperature and composition of the mantle transition zone (MTZ) beneath the United States. We investigate MTZ structure by mapping PtoS conversions at mineralogical phase changes using USArray waveform data and theoretical seismic profiles based on experimental constraints of phase transition properties as a function of temperature and composition. The width of the MTZ varies by about 35 km over the study region, corresponding to a temperature variation of more than 300 K. The MTZ is coldest and thickest beneath the eastern United States where high shear velocity anomalies are tomographically resolved. We detect intermittent PtoS conversions at depths of 520 km and 730 km. The conversions at 730km depth are coherent beneath the southeastern United States and are consistent with basalt enrichment of about 50%, possibly due to the emplacement of a fragment of an oceanic plateau (i.e., the Hess conjugate).